The reaction of [Cp*RhCl2]2, aniline, and a terminal alkyne : formation of cyclometalated rhodium(III) complexes - Kumaran, Elumalai (2014)
The reaction of [Cp*RhCl2]2 with an aniline (R′NH2) and a terminal alkyne (RCCH) afforded the N-containing cyclometalated rhodium complexes Cp*Rh(Cl)[N(R′)=C(CH2R)-CH=CR] via a hydroamination and a 1,2-insertion of an alkyne. A reaction pathway has been proposed on the basis of deuterium labeling experiments and computational studies.